Conhecendo o olho humano : um protótipo usado para o ensino de física voltado para a educação básica de jovens e adultos - Santos, Marcio Anicete dos (2016)
In this present work it has been developed a prototype of the human eye to help in teaching of physics applied in Basics Education of Youth and Adults- EJA. This prototype was divided in two parts: eyeball and a color reader, this last one aims to represent the function of the cones in the colors identification, using a digital electronics to aid in the assembly. It sought to achieve an product with emphasis in youth and adult education with ultimate goal of adapting a teaching methodology for these students who, for some reason, they didn´t have the opportunity to attend the school in appropriate time, aiming to ensure a meaningful learning. It aims to improve the quality of education, perfecting the pedagogical practice in Physics teaching, generate interest by EJA´s students by the content of this curricular component . The application and evaluation of this work were followed the presupposition of David Ausubel´s cognitive theory, according to which new ideas and information can be learned and retained as far as relevant and inclusive concepts adequately clear and available in the cognitive structure of the individual and serve, this way of anchorage to new ideas and concepts. It has been elaborated a support text to the teacher containing a lesson plan and a guide intending that teachers can apply and reproduce this prototype in order to contribute to the teaching practice and assisting in student learning this curriculum component.